2010
DOI: 10.1007/s11325-010-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in left ventricular cardiomyocyte loss induced by chronic intermittent hypoxia between spontaneously hypertensive and Wistar–Kyoto rats

Abstract: CIH causes cardiomyocyte loss in SHR mainly through cardiomyocyte necrosis. In WKY however, CIH simultaneously induces apoptosis and necrosis of cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
5
13
0
Order By: Relevance
“…In our study, IH raised myocardial levels of the inflammatory markers IL-6, TNF-α, MCP-1, and VCAM, similar to findings of previous studies [10, 58, 59]. Also, similar to previous studies [5, 8, 29], our study found that IH elevated levels of TBARTS and protein carbonyl, suggesting inflammation was accompanied by oxidative stress. These results suggest that IH-induced oxidative stress leads to increased myocardial inflammation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, IH raised myocardial levels of the inflammatory markers IL-6, TNF-α, MCP-1, and VCAM, similar to findings of previous studies [10, 58, 59]. Also, similar to previous studies [5, 8, 29], our study found that IH elevated levels of TBARTS and protein carbonyl, suggesting inflammation was accompanied by oxidative stress. These results suggest that IH-induced oxidative stress leads to increased myocardial inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…The IH process has previously been described [28, 29]. In brief, rats were housed in Plexiglas cylindrical chambers (length: 28 cm; diameter: 10 cm; volume: 2.4 L) with snug-fitting lids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IH is characterized as cyclic episodes of hypoxia of short duration followed by normoxia [4], leading to increased generation of intracellular reactive oxygen species (ROS) during re-oxygenation following hypoxia [5]. Previously, excess ROS accumulation was itself considered injurious because it can cause lipid peroxidation, protein oxidation, DNA damage [6] and intracellular ion deregulation [7], damaging cellular physiological function.…”
Section: Introductionmentioning
confidence: 99%
“…IH is associated with increased intracellular reactive oxygen species (ROS) generation during the reoxygenation phase [2]. IH has been reported to result in partially irreversible memory and learning impairments in both animals and humans [3].…”
Section: Introductionmentioning
confidence: 99%